Psectrosciara Kieffer in Mexico (Diptera: Scatopsidae): two new species and additional records for the genus - Huerta, Heron; Dzul-Manzanilla, Felipe; Manrique-Saide, Pablo; de Souza Amorim, Dalton (Zootaxa, 2019)
Two new species of Psectrosciara Kieffer from Mexico—Psectrosciara ahuatla sp. nov. and Psectrosciara otumba sp. nov., both belonging to the scatopsiformis-group, are described and illustrated based on males and females collected in Neotropical (Acapulco and Nuxco in the State of Guerrero) and Nearctic (Coyotepec, in the State of Mexico) areas in Mexico. We have a new record of Psectrosciara serrata Cook from Jalisco (in the Biological Station of Chamela) and females from different parts of Mexico. A key for the species of Psectrosciara from Mexico is presented.